Material Needs of Emergency Department Patients: A Systematic Review. (5th February 2018) - Malecha, Patrick W.; Williams, James H.; Kunzler, Nathan M.; Goldfrank, Lewis R.; Alter, Harrison J.; Doran, Kelly M.
Abstract: Background: Interest in social determinants of health (SDOH) has expanded in recent years, driven by a recognition that such factors may influence health outcomes, services use, and health care costs. One subset of SDOH is material needs such as housing and food. We conducted a systematic review of the literature on material needs among emergency department (ED) patients in the United States. Methods: We followed PRISMA guidelines for systematic review methodology. With the assistance of a research librarian, four databases were searched for studies examining material needs among ED patients. Two reviewers independently screened titles, abstracts, and full text to identify eligible articles. Information was abstracted systematically from eligible articles. Results: Forty‐three articles were eligible for inclusion. There was heterogeneity in study methods; single‐center, cross‐sectional studies were most common. Specific material needs examined included homelessness, poverty, housing insecurity, housing quality, food insecurity, unemployment, difficulty paying for health care, and difficulty affording basic expenses. Studies overwhelmingly supported the notion that ED patients have a high prevalence of a number of material needs. Conclusions: Despite some limitations in the individual studies examined in this review, the plurality of prior research confirms that the ED serves a vulnerable population with high rates of material needs. Future research is needed to better understand the role these needs play for ED patients and how to best address them.